The COBIT 5 Analysis on World Muslim Scientists Index Web Application - Miftahurrizqi Miftahurrizqi; Ika Safitri Windiarti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The web mobile aims to access data services using mobile devices connected to a cellular telecommunications network. One of the knowledge that needs to be obtained by the wider community, especially the younger generation of Islam, is knowledge of World Muslim Scientists. This World Muslim scientist himself has a very great power to influence the younger generation to be more creative and innovate accompanied by their pride in their predecessors. Information on the World Muslim Scientists Index needs to be packaged to make it attractive. Web Mobile can introduce the World Muslim Scientists Index which is interesting and attractive in delivering information. The problem in several previous studies related to application design is that the application design is not audited for its governance, so it is at risk of not being planned and managed properly. Therefore, in this study, the authors develop the design and implementation of the World Muslim Scientists Index, accompanied by a governance audit in its design using the COBIT 5 Framework method in the PO (Plan and Organize) domain. The result of this research is that the design and management of this application is already at maturity level 4, namely Manage, which means that it is well planned and managed.